2021
DOI: 10.51470/plantarchives.2021.v21.s1.086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic and Potassium Fertilization on Potato Yield and Quality

Abstract: Potato is considered strategic vegetable crop in the entire world. So, two field experiments were conducted in the experimental farm, Faculty of Agriculture, Mansoura University to study the effect of organic fertilization and foliar application with potassium (K) as well as rates of K soil fertilization and their interaction on vegetative growth (plant height, No of leaves/plant, fresh and dry weight), leaves chemical composition (Chlorophyll a, b, a+b, N, P and K), tuber yield (plant yield, No. of tuber/plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The surface morphology of HZ‐CELL or M‐HZ‐CELL was indicated using SEM analysis. As shown in Figure 3a, the SEM of the blank cotton fabric looks to have smooth fibers 43 . Figure 3b–f shows agglomerated particles on the HZ‐CELL and the M‐HZ‐CELL (M is Ni, Cu, Zn, or Cd) as an indication for the modification of cotton fabric.…”
Section: Resultsmentioning
confidence: 91%
“…The surface morphology of HZ‐CELL or M‐HZ‐CELL was indicated using SEM analysis. As shown in Figure 3a, the SEM of the blank cotton fabric looks to have smooth fibers 43 . Figure 3b–f shows agglomerated particles on the HZ‐CELL and the M‐HZ‐CELL (M is Ni, Cu, Zn, or Cd) as an indication for the modification of cotton fabric.…”
Section: Resultsmentioning
confidence: 91%
“…Also, it can increase soil aggregates and thereby raising the leaching of salts away from the root zone. The superiority of enhanced compost compared to plant residues compost may be attributed to that enhanced compost had lower C/N ratio compared with plant residues compost as well as its high content from nutrients (Abd El-Hady et al, 2021;Ghazi et al, 2021;Seadh et al, 2021 andOmar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Commercial products like NanoMax-NPK and Ferbanat utilize organic micronutrients, vitamins, and probiotics to enhance crop vitality and root zone activities. During the 2012-2013 growing season, research outlined in [11] investigated the influence of nano-fertilizer (Pharmks®) and humic acid treatments on Nigella sativa L. The study revealed notable impacts of varying humic acid levels on several yield parameters, including seed weight, biological yield, number of capsules per plant, seeds per capsule, and harvest index. Humic acid treatments at concentrations of 3 and 6 ml/l produced the best yields.…”
Section: Organic Nanofertilizersmentioning
confidence: 99%
“…Nano-Particle Used Parameter Obtained Result Obtained [11] Humic acid Yield parameters (Nigella sativa L.)…”
Section: Studymentioning
confidence: 99%